2010
DOI: 10.1007/s12301-010-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasound diagnosis after blunt scrotal trauma (10 years experience)

Abstract: Objectives:To evaluate the role of ultrasonography (US) and its accuracy, sensitivity and specificity for the diagnosis of testicular rupture after blunt scrotal trauma. Moreover, tunica albuginea breach, testicular hematoma, testis avulsion, epididymal injuries and hematocele are particularly examined. Patients and Methods: Between 1998 and 2008, 24 patients presented to Suez Canal University Hospital after blunt scrotal trauma and underwent surgical exploration. All patients had an emergency scrotal US exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Higher rates of adverse outcomes (impaired fertility, hypogonadism, testicular loss) were associated with this delay in care. 8 In the case of testicular rupture, salvage rates are as high as 90% when surgery is performed within 72 hours. When surgical intervention is delayed beyond 72 hours, salvage rates decline to approximately 45%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher rates of adverse outcomes (impaired fertility, hypogonadism, testicular loss) were associated with this delay in care. 8 In the case of testicular rupture, salvage rates are as high as 90% when surgery is performed within 72 hours. When surgical intervention is delayed beyond 72 hours, salvage rates decline to approximately 45%.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of US for the evaluation of these pathologies has been established through retrospective studies that have compared sonographic findings against those found on subsequent scrotal exploration, the traditional gold standard for diagnostic and therapeutic evaluation. 6 , 8 The post-traumatic ultrasonic evaluation for hematocele has been shown to be 85–87% sensitive and 75–89% specific according to two studies of 24 and 33 patients, respectively. 6 , 8 Three studies, consisting of 33, 65, and 24 patients, have reported the sonographic findings for testicular rupture to be 92–100% sensitive while being 50–93.5% specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations